Dissipative Soliton Generation From Yb-Doped Fiber Laser Modulated by Mechanically Exfoliated NbSe2 - Chen, Longlong; Du, Lin; Li, Jie; Yang, Lingling; Yi, Qian; Zhao, Chujun (Frontiers in Physics, 2020)
We experimentally demonstrated that the stable dissipative solitons can be generated from the Yb-doped fiber laser with the interaction of mechanically exfoliated NbSe2 and the evanescent field of the D-shaped fiber. The modulation depth of the saturable absorber with exfoliated layered NbSe2 is 17.26% and the saturation intensity is 34.8 kW/cm2, respectively. With the proposed saturable absorber, the Yb-doped fiber laser can deliver stable dissipative soliton with pulse duration 174 ps, repetition rate 14.7 MHz and signal-to-noise ratio 59.8 dB at the pump power 300 mW. The experimental results provide an insight for the ultrafast non-linear optical response of layered transition metal dichalcogenide, which may provide strategies for developing high-performance ultrafast non-linear optical devices.